THE ROLE OF EMPLOYEE ENGAGEMENT IN IMPROVING EMPLOYEE PERFORMANCE - Moch. Riski; Andi Indriani Ibrahim; Fatlina Zainuddin; Ponirin (RADJA PUBLIKA, 2026)
This article comprehensively examines the role of employee engagement (EE) in improving employee performance through a systematic literature review approach . The study focuses on three dimensions of employee engagement : vigor, dedication, and absorption, and their impact on individual and organizational performance. In addition to presenting a synthesis of empirical findings, this article specifically explains the statistical formulas underlying each cited research figure, including the Pearson correlation coefficient, the path coefficient in Structural Equation Modeling, the effect size formula in meta-analysis, significance tests (t-test and p-value), and the coefficient of determination (R²). The study results indicate that employee engagement has a positive and significant effect on employee performance. Understanding the formulas behind these figures is important so that the study results can be read critically, replicated, and used as a basis for appropriate managerial decision-making.